2005
DOI: 10.1590/s0102-86502005000700018
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da simpaticotomia endoscópica sobre as artérias carótidas e vertebrais na terapêutica cirúrgica da hiperidrose primária

Abstract: Our date demonstrated that CD5 expression can help distinguish among B-CLL from HCL and B-PLL, but is similar expressed in MCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In other studies a positive relationship between heredity and primary hyperhidrosis was found 1,12 . One report showed that 15.3% of adolescents had a positive family history for hyperhidrosis 8 .…”
Section: Results Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In other studies a positive relationship between heredity and primary hyperhidrosis was found 1,12 . One report showed that 15.3% of adolescents had a positive family history for hyperhidrosis 8 .…”
Section: Results Resultsmentioning
confidence: 66%
“…P rimary hyperhidrosis is a benign disease with a prevalence of 1% in the Western world, characterized by excessive production of sweat in one or more anatomical regions. It has a genetic (3-57%) and environmental backgrounds, significant climatic influences being observed in patients with this disease [1][2][3] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of primary hyperhidrosis may be conservative, through drugs and psychotherapy, or surgical, considered definitive. The gold standard treatment is endoscopic thoracoscopic sympathectomy (ETS) [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…The ETS consists of the endoscopic surgical approach of the paravertebral sympathetic chain at the level of T3(G3) or T4(G4) [2]. When performed on T3(G3), it presents greater efficacy of the procedure, yet higher rates of compensatory hyperhidrosis.…”
Section: Introductionmentioning
confidence: 99%